Cardiorenal Signaling Pathways in Heart Failure: Good and Bad News - Martin Rosas-Peralta; Silvia Palomo-Piñón; Gabriela Borrayo Sánchez; Gilberto Pérez Rodríguez; José Ramón Paniagua-Sierra (Journal of Hypertension and Cardiology, 2016)
This article reviews heart–kidney signaling in heart failure, contrasting adaptive and maladaptive pathways. It discusses neurohormonal activation, fibrosis, and emerging therapeutic targets.
Keywords: Heart Failure